Stemness and angiogenic gene expression changes of serial-passage human amnion mesenchymal cells - Fatimah, SS; Tan, GC; Chua, K; Fariha, MMN; Tan, AE; Nur Fariha Mohd Manzor (Academic Press Inc Elsevier Science, 2024)
Background: Particular attention has been directed towards human amnion mesenchymal stem cells (HAMCs) due to their accessibility, availability and immunomodulatory properties. Therefore, the aim of the present study was to determine the temporal changes of sternness and angiogenic gene expressions of serial-passage HAMCs. Methods: HAMCs were isolated from human term placenta and cultured in serial passages in culture medium supplemented with 10% fetal bovine serum. Morphological analysis, growth kinetic and CFU-F assay of HAMCs were assessed. In vitro differentiation and the immunophenotype of HAMCs at P5 were also analyzed. Quantitative PCR was used to determine the sternness, angiogenic and endothelial gene expression of cultured HAMCs after serial passage. Results: Cultured HAMCs displayed intermediate epitheloid-fibroblastoid morphology at an initial culture and the fibroblastoid features became more pronounced in later passages. They showed high clonogenic activity and faster proliferation at later passages with colony forming efficiency of 0.88%. HAMCs were successfully differentiated into adipocytes, osteocytes and neuron-like cells. Most HAMCs expressed CD9, CD44, CD73, CD90 and HLA-A,B,C but negligibly expressed CD31, CD34, CD45, CD117 and HLA-DR,DP,DQ. After serial passage, sternness genes Oct-3/4, Sox-2, Nanog3, Rex-1, FGF-4 and FZD-9 expressions significantly decreased. Of the angiogenic genes PECAM-1, bFGF, eNOS, VEGFR-2, VEGF, and vWF expressions also decreased significantly except angiopoietin-1 which significantly increased. No significant differences were observed in ABCG-2, BST-1, nestin, PGF and HGF expressions after serial passage. Conclusion: These results suggested that cultured HAMCs could be an alternative source of stem cells and may have the potential for angiogenesis and hence its use in stem-cell based therapy. (C) 2012 Elsevier Inc. All rights reserved.